The Referendum. General Concept and Legal Regulation in Peru - Wieland Conroy, Hubert (2008)
The purpose of this paper is to develop the concept of a referendum as an institution; In addition, it analyzes the regulations that regulate it in Peru. In this sense, first, the background of this is analyzed, since it is established as an institution only in the Constitution of 1993. However, its origins date back to the late nineteenth century. Second, the author develops the evolution of the concept. The origin of the term is found in the Latin expression of ad referendum, which meant that the closing of an agreement depended on its ratification. However, this definition did not imply that such ratification was necessarily given by the people. This is how the term is adapted, to finally designate the ratification through popular consultation. In third and last place, the author develops the regulation regarding the referendum. The regulations are analyzed by distinguishing between two groups: i) by citizen initiative and ii) by institutional initiative. Following this line, the first group analyzes the main rules that can be applied to this type of referendum. These are three mainly: The Political Constitution of Peru, the Organic Law of Elections (LOE) and the Law of Rights of Participation and Control of Citizens (LDPCC). In addition, the assumptions are developed in which this can be applied: the reform of the Constitution, the approval of norms with the rank of law, the approval of municipal ordinances and the modification of regions. In the second group, referendum by institutional initiative, are those that are convened by the Congress of the Republic, by the Executive Power or, in some cases, by Municipal Councils.